REKONSTRUKSI PERJANJIAN FIDUSIA ATAS BENDA BERGERAK YANG DIDAFTARKAN BERDASARKAN NILAI KEADILAN - Sugiatno . (UNISSULA, 2014)
Fiduciary is one form of collateral material that is very well known in the business life in the form of transfer of ownership of an object on the basis of trust. The rule of law in positive law in Indonesia is deemed no longer compatible with the current legal developments, particularly in supporting the economy and the business world. This study use socio-legal studies approach. Socio-legal studies have ultimate goal related to the objective essence of the law, through a reconsideration or a new discovery of legal norms should prevail and that it should not apply. The results obtained in this study: (1) Construction law fiduciary agreement on moving objects according to Law No. 42 of 1999 concerning fiduciary already registered implemented through two (2) phases, namely the loading phase and phase fiduciary guarantee registration. (2) reconstruction of the Articles of Law Number 42 Year 1999 on Fiduciary namely Reconstruction of Article 5, paragraph 1 that the parties should come in the fiduciary deed, the reconstruction of article 29 (1a and c) that the creditor can take the object of fiduciary without dispute to pay off the debt of the debtor. In addition, the reconstruction of the object of Article 31 that the fiduciary are objects that are sold in exchange of sales made on bursa effect until paid off its debts